Use the Robust method to solve the problem of fuzzy translocation to take the right decision to reduce the cost of transportation in medical field by quantization method - Abbas Hussein Batikh (Journal of Madenat Alelem University College, 2014)
The transportation models are considered as the important methods in Operations Research that play an essential role in making an optimal decision in the transport of resources, requirements, and tasks to those required, that execute those tasks to attain the least cost of transport accordingly. This task is pawned by the knowledge of the costs, requests and displayed quantities related to the process of transportation. The transportation costs and their required and displayed quantities are not clear-cut generally. For the purpose of activating the transportation models in the process of decision-making, we utilize Fuzzy theory to treatment of the transportation models use way (Robust) in the process of decision-making, which shows that the costs and required and displayed quantities are sping-tailed lizard and unclear .